Functional significance of the electrocorticographic auditory responses in the premotor cortex - Tanji, Kazuyo; Sakurada, Kaori; Funiu, Hayato; Matsuda, Kenichiro; Kayama, Takamasa; Ito, Sayuri; Suzuki, Kyoko (Frontiers in Neuroscience, 2015)
Other than well-known motor activities in the precentral gyrus, functional magnetic resonance imaging (fMRI) studies have found that the ventral part of the precentral gyrus is activated in response to linguistic auditory stimuli. It has been proposed that the premotor cortex in the precentral gyrus is responsible for the comprehension of speech, but the precise function of this area is still debated because patients with frontal lesions that include the precentral gyrus do not exhibit disturbances in speech comprehension. We report on a patient who underwent resection of the tumor in the precentral gyrus with electrocorticographic recordings while she performed the verb generation task during awake brain craniotomy. Consistent with previous fMRI studies, high-gamma band auditory activity was observed in the precentral gyrus. Due to the location of the tumor, the patient underwent resection of the auditory responsive precentral area which resulted in the post-operative expression of a characteristic articulatory disturbance known as apraxia of speech (AOS). The language function of the patient was otherwise preserved and she exhibited intact comprehension of both spoken and written language. The present findings demonstrated that a lesion restricted to the ventral precentral gyrus is sufficient for the expression of AOS and suggest that the auditory-responsive area plays an important role in the execution of fluent speech rather than the comprehension of speech. These findings also confirm that the function of the premotor area is predominantly motor in nature and its sensory responses is more consistent with the ‘sensory theory of speech production’, in which it was proposed that sensory representations are used to guide motor-articulatory processes.